Ecological Role of an Offshore Industry Artificial Structure - Gates, Andrew R.; Horton, Tammy; Serpell-Stevens, Amanda; Chandler, Chester; Grange, Laura J.; Robert, Katleen; Bevan, Alexander; Jones, Daniel O. B. (Frontiers in Marine Science, 2019)
Decommissioning of oil and gas infrastructure in all major basins globally has focused attention on its importance as hard substratum on continental shelf and slope habitats. Observational studies are needed to improve understanding of faunal assemblages supported by offshore infrastructure and better predict the effect of removal. Here we present results from visual inspection and physical sampling of a small oil and gas industry structure decommissioned from an oil field in the North East Atlantic. This is supported by observations of similar structures nearby and by photographs of the surrounding seabed from environmental baseline surveys. The structure supported a reasonably high biomass and diversity of invertebrates (>10 kg and > 39 macrofaunal and 17 megafaunal species) and fishes (>20 kg biomass and > 4 species). The invertebrate megafaunal species present on the structure were a sub-set of the hard substratum fauna observed on surrounding seabed. Porifera were absent from the structure. Biological succession in the first two years occurred as follows. Sparse colonies of the hydroid Obelia sp. stet were early colonisers then subsequent development of thick hydroid turf (Obelia sp. stet. and Halecium sp. stet.) supported a diverse invertebrate assemblage (2654 individuals kg wet mass-1) dominated by saddle oysters (Pododesmus squama (Gmelin, 1791) and Heteranomia sp. stet.)) and scale worms (Hormothoe spp.). Percentage cover of hydroid turf varied significantly over the structure, with most growth on sections exposed to strongest currents. Commercially important fish species present around the structure included Gadus morhua (Atlantic cod), Pollachius virens (saithe) and Lophius piscatorius (monkfish). Studies of artificial structures such as this provide much needed data to understand their role in the ecology of seafloor habitats and inform environmental decision making on all stages of industry from exploration to decommissioning. We show that the ecological role of the decommissioned three-dimensional structures was to enhance the biomass of a sub-set of epifaunal invertebrates found in the area. This supported diverse associated macrofaunal organisms, providing a food source for motile invertebrates and fishes in an area where background hard substratum can be lost through the impacts of drilling.